A Fortified Food Can Be Replaced by Micronutrient Supplements for Distribution in a Mexican Social Protection Program Based on Results of a Cluster-Randomized Trial and Costing Analysis. (3rd December 2019) - Neufeld, Lynnette M; García-Guerra, Armando; Quezada, Amado D; Théodore, Florence; Bonvecchio Arenas, Anabelle; Islas, Clara Domínguez; Garcia-Feregrino, Raquel; Hernandez, Amira; Colchero, Arantxa; Habicht, Jean Pierre
ABSTRACT: Background: Despite positive nutrition impacts, the prevalence of malnutrition among beneficiaries of Mexico's conditional cash transfer (CCT) program remains high. Greater nutrition impact may have been constrained by the type of nutritional supplements provided. Objective: The objective of this study was to inform a potential modification to the supplements distributed to pregnant and lactating women and children. Methods: Impact was assessed using 2 cluster-randomized trials (pregnant women, children) run simultaneously. Communities ( n  = 54) were randomly assigned to the fortified foods provided by the program (Nutrivida women, Nutrisano children) or alternatives: tablets (women), syrup (children), or micronutrient powders for women (MNP-W) and children (MNP-C). Each supplement for women/children contained the same micronutrients based on the formulations of Nutrivida and Nutrisano, respectively. Pregnant women (aged >18 y) were recruited before 25 weeks of gestation and followed to 3 mo postpartum. Children aged 6–12 mo were recruited and followed to age 24 mo. Primary outcomes were anemia for women and length growth for children. Statistical analyses appropriate for cluster-randomized designs were used, and structural equation modeling to estimate dose-response effects. Supplement costs per beneficiary (daily dose for 18 mo) were estimated for production and distribution. Results: There was no significant difference in change of anemia prevalence between supplement groups in women, or in length growth between groups in children. One daily dose of any supplement was associated with 0.8 cm greater length growth. From baseline to age 24 mo, the prevalence of anemia in the Nutrisano, syrup, and MNP-C groups decreased by 36.7, 40.8, and 37.9 percentage points, respectively (within-group, P < 0.05; between groups, P  > 0.05). Costs per beneficiary ranged from $12.1 (MNP-C) to $94.8 (Nutrivida). Conclusions: The CCT program could distribute alternative supplements at lower cost per beneficiary without compromising potential for impact. Acceptance among beneficiaries should also be considered in choice of alternatives. This trial was registered at www.clinicaltrials.gov as NCT00531674.